Study the Effects of Reactive Materials Replacement on Some Properties of Cement Mortar - Kadhim, Mohammed J.; Mohammed Jawad, Raeid K.; Kamal, Hamza M. (Science Journal of University of Zakho, 2018)
This study involves natural–materials replacement and its reaction with cement mortar behavior for many mortar samples under variable curing time with constant water to cement ratio (W/C = 0.5).In this researchsomeproperties such as (compressive strength the surface hardness and water absorption test), were affected by adding small ratios ofpowder (from (RHA) and (BRP) particles)as replacements to the Ordinary Portland Cement (OPC) / type (I). The percentages of natural materials additives replacement on the mixture of mortar include (0, 5, 10, 15 and 20%) with constant (W/C) ratio. Also the amount of the fine aggregate used was three times the amount of cement. The results showed that, the compressive strength and splitting tensile strength and water absorption of the mortars for (replacement) gives better properties than mortar without replacement in all tests. Best enhancements in properties for mortars with pozzalanic replacements were achieved at (15%) for (RHA) and 10% for (RBP) replacement from weight of cement.